2019
DOI: 10.1177/1049909119858352
|View full text |Cite
|
Sign up to set email alerts
|

A Tripartite Model of Community Attitudes to Palliative Care

Abstract: Background: Despite a growth in palliative care services, access and referral patterns are inconsistent and only a minority of people who would benefit from such care receive it. Use of palliative care is also affected by community attitudes toward palliative care. As such, determining community attitudes toward palliative care is crucial. We also need to determine what predicts attitudes in order to provide appropriate information and education. Objectives: The 2 research questions were: (1) What are communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Some participants in the present study appeared influenced by having observed a ‘bad death’ (Wilson & Hewitt, 2018), or had views on what a ‘good death’ (Read & MacBride-Stewart, 2018) should look like, both highly individualised and subjective concepts usually based on experience. Some proposed VAD as a way of mitigating suffering (Beuthin et al, 2018) with palliative care proposed by some as a way of addressing pain and suffering (O'Connor et al, 2019), but others finding it to be lacking and not always accessible or adequate to meet all needs (Hayry, 2018). Being in pain at the end of life was certainly a consideration by some, with VAD seen as a way of avoiding this.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants in the present study appeared influenced by having observed a ‘bad death’ (Wilson & Hewitt, 2018), or had views on what a ‘good death’ (Read & MacBride-Stewart, 2018) should look like, both highly individualised and subjective concepts usually based on experience. Some proposed VAD as a way of mitigating suffering (Beuthin et al, 2018) with palliative care proposed by some as a way of addressing pain and suffering (O'Connor et al, 2019), but others finding it to be lacking and not always accessible or adequate to meet all needs (Hayry, 2018). Being in pain at the end of life was certainly a consideration by some, with VAD seen as a way of avoiding this.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature on awareness of and attitudes toward palliative care are mainly descriptive, outlining health care professionals and the publics' awareness, attitudes and perceptions toward palliative care with mixed results [e.g., ( 12 , 21 – 25 )]. While some research found that most people had positive attitudes and good knowledge of palliative care ( 24 , 25 ), other studies found the opposite ( 12 , 21 , 23 , 26 ). Thus, it is important to address the prior inconsistent findings and further examine public awareness of and attitudes toward palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this study, the tripartite model of attitudes was selected as the conceptualized structure of dementia attitudes to gain a comprehensive understanding of how people think about dementia or PLWD (Rosenberg et al, 1960). This model, developed by Rosenberg et al, is widely used to understand attitudes towards various diseases and palliative care and guided the development of the Dementia Attitude Scales (O'Connor et al, 2019;O'Connor and McFadden, 2010). In this model, attitude consists of three measurable components: affective, cognitive, and behavioral.…”
Section: Introductionmentioning
confidence: 99%